Propylparaben applied after pilocarpine-induced status epilepticus modifies hippocampal excitability and glutamate release in rats - Santana-Gómez, César Emmanuel (2017)
Propylparaben (PPB) induces cardioprotection after ischemia–reperfusion injury by inhibiting voltage-dependent Na+ channels. The present study focuses on investigating whether the i.p. application of 178 mg/kg PPB after pilocarpine-induced status epilepticus (SE) reduces the acute and long-term consequences of seizure activity. Initially, we investigated the effects of a single administration of PPB after SE. Our results revealed that compared to rats receiving diazepam (DZP) plus vehicle after 2 h of SE, animals receiving a single dose of PPB 1 h after DZP injection presented 126% (p < 0.001) lower extracellular levels of glutamate in the hippocampus. This effect was associated with an increased potency of low-frequency oscillations (0.1–13 Hz bands, p < 0.001), a reduced potency of 30–250 Hz bands (p < 0.001) and less neuronal damage in the hippocampus. The second experiment examined whether the subchronic administration of PPB during the post-SE period is able to prevent the long-term consequences of seizure activity. In comparison to animals that were treated subchronically with vehicle after SE, rats administered with PPB for 5 days presented lower hippocampal excitability and interictal glutamate release, astrogliosis, and neuroprotection in the dentate gyrus. Our data indicate that PPB, when applied after SE, can be used as a therapeutic strategy to reduce the consequences of seizure activity.